Pengaruh Perebusan Telur Pindang Telur Ayam Ras dengan Penggunaan bahan penyamak Daun Jambu Biji (Psidium guajava L.) dan Daun Jati (Tectona grandis) terhadap Kualitas Organoleptik: The Effect of Teak (Tectona grandis) and Guava (Psidium guajava L.) Leaves on The Quality of Pindang Eggs - Lestari, Rini; Mudawaroch, Roisu Eny; Rinawidiastuti, Rinawidiastuti (Jurnal Riset Agribisnis dan Peternakan, 2022)
This study aims to determine the level of tannins at the level of guava leaves (Psidium guajava) and teak leaves (Tectona grandis). The ingredients are 60 eggs, teak leaves, guava leaves, and salt. The treatments given were 0:100 (B0J100), 25:75 (B25J75), 50:50 (B50J50), 75:25 (B75J25), and 100:0 (B100J0). The design in this study was a Completely Randomized Factorial Design (CRD) with 5x4 with 4 replications. The first factor was the level of guava and teak leaves with a ratio of 0:100, 25:75, 50:50, 75:25 and 100:0. The second factor is the length of storage consisting of L0 = 0 days, L5 = 5 days, L10 = 10 days and L15 = 15 days. The color value of boiled eggs on storage time was significantly different , the color value ranged from 2.51-3.28. The value of egg aroma at tanning level was not different and the storage time was significantly different with aroma values ranging from 2.37 to 3.15. The texture values of boiled eggs, both tanning level and storage time, were significantly different with values ranging from 0.13 to 0.34. The taste value of boiled eggs, both tanning level and storage time, were significantly different with values ranging from 2.50 to 2.94. The conclusion is that there is an effect of adding teak leaves and guava seeds to the organoleptic test. Suggestions to increase the level of concentration so that the shelf life is longer.